De la fiction d’une absence à l’autofiction d’une présence : l’écriture de la mort de la mère dans l’œuvre de Jorge Semprun - Ponchon, Catherine (Quêtes littéraires, 2011)
“Night has enshrouded my childhood” write Jorge Semprun. Civil War and exile have erased any trace of the childhood he spent in Madrid. What was left to the writer were only flashes of memory and an old picture of his mother. Jorge Semprun was eight years of age when his mother died of septicemia. Through writing, thirty years later, he was able to evoke her death, but how was he to tell about her absence? Between fiction and reality, five of Jorge Semprun’s novels recreate his childhood. His mother will first of all be an absence or an implicit presence behind his relating the city of his childhood. Having set the scene, ghostly characters whose identities are undefined but whose discourses become more and more outlined will appear. The mother will become a nostalgic absence. Her features, her character will be sketched out. Jorge Semprun will move forward hiding behind the multiple identities of his characters and the freedom which fiction provides him. It will be up to the last character, a fictive double of the writer, to find the last traces of a mother who has turned into a haunting presence.